Spray-dried Ancellotta red wine : natural colorant with potential for food applications - Álvarez Gaona, Izmari Jasel (2019)
Fil: Álvarez Gaona, Izmari Jasel. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina